PENGARUH HARGA, LOKASI DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PENGGUNA JASA RENT CAR (Studi Kasus Pada Rizqy Rent Car Malang) - Agus Dimas Aripin; Muhammad Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThis paper be discuss how the price, location and produc attribute simultaneously influences toward costumer decision of rent car (study case of Rizky Rent Car Malang). And also to know how the price, location and product attribute partially influences toward costumer decision of Rent Car (study case of Rizqy Rent Car Malang). To achive the disered goal, this paper will be analyzed by multiple linier regression.Based on the analysis of hypothesis result, the price, location and product attribute simultaneously influence significant toward costumer decision of Rent Car (study case of Rizqy Rent Car Malang) and so it was partially influences toward costumer decisionKeywords : price, location, product attribute and costumer decision